Simulation of Cascaded H-Bridge Multilevel Inverter Based DSTATCOM - Rammohan Rao Makineni; C.N. Bhaskar (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents an investigation of five-Level Cascaded H – bridge (CHB) Inverter as Distribution Static Compensator (DSTATCOM) in Power System (PS) for compensation of reactive power and harmonics. The advantages of CHB inverter are low harmonic distortion, reduced number of switches and suppression of switching losses. The DSTATCOM helps to improve the power factor and eliminate the Total Harmonics Distortion (THD) drawn from a Non-Liner Diode Rectifier Load (NLDRL). The D-Q reference frame theory is used to generate the reference compensating currents for DSTATCOM while Proportional and Integral (PI) control is used for capacitor dc voltage regulation. A CHB Inverter is considered for shunt compensation of a 11 kV distribution system. Finally a level shifted PWM (LSPWM) and phase shifted PWM (PSPWM) techniques are adopted to investigate the performance of CHB Inverter. The results are obtained through Mat lab / Simulink software package.